Central nervous system commitment in Chagas disease - Useche, Yerly; Pérez, Ana Rosa; de Meis, Juliana; Bonomo, Adriana; Savino, Wilson (Frontiers in Immunology, 2022)
The involvement of the central nervous system (CNS) during human acute and chronic Chagas disease (CD) has been largely reported. Meningoencephalitis is a frequent finding during the acute infection, while during chonic phase the CNS envolvement is often accompanied by behavioral and cognitive impairments. In the same vein, several studies have shown that rodents infected with Trypanosoma cruzi (T. cruzi) display behavior abnormalities, accompanied by brain inflammation, in situ production of pro-inflammatory cytokines and parasitism in diverse cerebral areas, with envolvement of microglia, macrophages, astrocytes, and neurons. However, the mechanisms used by the parasite to reach the brain remain now largely unknown. Herein we discuss the evidence unravelling the CNS involvement and complexity of neuroimmune interactions that take place in acute and chronic CD. Also, we provide some clues to hypothesize brain infections routes in human and experimental acute CD following oral infection by T. cruzi, an infection route that became a major CD related public health issue in Brazil.